Gender rhetoric and Swedish police officers’ perceptions of victims - Eliasson, Michelle N. (International journal of comparative and applied criminal justice, 2024)
Sweden is considered to be among the most gender-equal countries globally and this philosophy influences every aspect of Swedish culture from medical care to foreign policy. It is not clear, however, to what extent this approach has been accepted or adopted by Swedish police officers. Using interviews with 27 Swedish police officers, this study explores the use of gender rhetoric in descriptions of victims. By performing an inductive thematic analysis, we find that officers have internalised the gender-equal approach but make statements alluding to adaptation of both gender-blind and gender-aware rhetoric when describing victims. When describing their own personal experiences with victims, officers use language informed by gender stereotypes and gender performativity suggesting that these principles have not been fully adopted.